ANALYSIS OF DIFFERENCES IN THE EFFECTIVENESS OF GIVING RED BEET JUICE (BETA VULGARIS L) AND CUCUMBER JUICE (CUCUMIS SATIVUS) ON REDUCING BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Wahyuni, Srie; Wati, Rahma; Hidayatullah, Mhd. (Transpublika Publisher, 2023)
Hypertension is a serious health issue worldwide, leading to cardiovascular diseases like heart attack, heart failure, stroke, and kidney disease. To prevent hypertension, a combination of pharmacological and non-pharmacological methods is necessary, including adopting a healthy lifestyle and consuming herbal plants. For instance, cucumber juice therapy and a mix of beetroot and pineapple juice are commonly used. This study aims to compare the effects of red beet juice and cucumber juice on the blood pressure of hypertensive patients in Drien Tujoh Village, Tripa Makmur District, Nagan Raya Regency in 2023. The research involved 30 hypertensive patients over 35 years old, divided into two groups. The results showed a significant difference in blood pressure before and after the intervention with beetroot juice and cucumber juice. This indicates that both interventions can help lower blood pressure in hypertensive patients.